1974
DOI: 10.1111/j.1600-0560.1974.tb00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Light and Electron Microscopic Study of Riehl's Melanosis. Possible Mode of its Pigmentary Incontinence

Abstract: Four cases of Riehl's melanosis were studied with light and electron microscopes. The results obtained were as follows: Unmyelinated nerve fibers were found in both the epidermis and the dermis, and the Schwann cells enclsing the axons contained melanosomes. A peculiar pigment cell was found in the epidermis, it was thought to be a macrophage phagocytizing melanosomes from the extracellular spaces. A melanophage in contact with a keratinocyte through the gaps of the basal lamina was observed. It was suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…This is confirmed by the observation that melanin accumulates around hair follicles in the dermis with aging (Fig. 5F), which is probably due to a poorly defined process known as pigmentary incontinence described in inflammatory skin diseases (Schaumberg-Lever and Lever, 1973;Nagao and Iljima, 1974;Masu and Seiji, 1983) and in senile lentigo (Ünver et al, 2006). In addition, mice.…”
Section: Discussionsupporting
confidence: 57%
“…This is confirmed by the observation that melanin accumulates around hair follicles in the dermis with aging (Fig. 5F), which is probably due to a poorly defined process known as pigmentary incontinence described in inflammatory skin diseases (Schaumberg-Lever and Lever, 1973;Nagao and Iljima, 1974;Masu and Seiji, 1983) and in senile lentigo (Ünver et al, 2006). In addition, mice.…”
Section: Discussionsupporting
confidence: 57%
“…Amyloid-like filament masses which could not be differentiated from the true amyloid in PLCA were observed in four patients. While amyloid stainings such as congo red and thioflavin T stains were entirely negative in our cases, Nagao and Iijima (1974) reported that thioflavin T-positive amyloid were found in their cases of Riehl's melanosis. And it is known in general that the tinctorial properties of amyloid are not always consistent (Nakagawa 1965;Rook et al 1972).…”
Section: Discussionmentioning
confidence: 70%
“…They speculated that Civatte bodies might be converted into amyloid or in some way provide a matrix for the formation of amyloid. In Riehl's melanosis, Nagao and Iijima (1974) found Civatte bodies and amyloid, and suggested that these two substances were pathogenetically related. Recently, a case with lichen amyloidosus on the legs and Riehl's melanosis-like lesion on the face was studied under the electron microscope, and it was concluded that Civatte bodies could be converted into amyloid under certain conditions like Riehl's melanos is because it was found that there were transitional forms between Civatte body and amyloid in the skin specimen from the face (Masu et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Riehl's melanosis typically involves the face with a brownish-grey pigmentation; biopsy might be expected to show interface change and liquefaction basal cell degeneration with a moderate lymphohistiocytic infiltrate, melanophages and pigmentary incontinence in the upper dermis. It is usually associated with cosmetic use and may be considered synonymous with pigmented allergic contact dermatitis of the face (6,7). Berloque dermatitis is considered to be caused by a photoirritant reaction to bergapentin; it may affect the sun-exposed areas of the face, neck and arms.…”
Section: Sirmentioning
confidence: 99%